The Constraints Used of E-Money for Female Recipients of Non-Cash Social Assistance Programs in Indonesia - Widiastuti, Tuti (International Journal of Psychosocial Rehabilitation, 2020)
The Family Hope Program (Program Keluarga Harapan/PKH) is a social assistance program that uses e-money in an attempt to break the chain of poverty, with increased quality of human resources through education and health. The main objective of the paper is to gain an idea of how culture shock occurs due to differences between the individual's expectations and the reality that there are difficulty assistance recipients, particularly female recipients of e-money, in the culture of the Malingping Sub-district of Lebak, Indonesia. The case in this study is seen in the perspective of genderlect styles. This research uses qualitative approaches with the method of grounded theory with collecting information via in-depth interviews with key informants and study field documents. This research shows that individuals pass through four levels of culture shock: the optimistic phase, a phase of cultural issues, the recovery phase, and the adjustment phase. In the end, the individual can recognise the good things within a new culture of PKH; can appropriately cope with new cultural experiences. Culture shock process can be more handled through good relationship between PHK’s social workers and female recipients of non-cash social assistance programs. Therefore, the distribution of social grants can fulfil the principle of accuracy, reaching the right people with the needed timely amounts and appropriate administration..